2021
DOI: 10.1039/d1ra06148h
|View full text |Cite
|
Sign up to set email alerts
|

Naproxen release aspect from boron-doped carbon nanodots as a bifunctional agent in cancer therapy

Abstract: In this present study, boron–carbon nanodots were synthesized by the hydrothermal method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
1
1
0
Order By: Relevance
“…Next, morphology analysis of Cu-CDs shows the topographic images of Cu-CDs based on the AFM result, which demonstrated that the sperical topographic height (figures 3(a)-(b) dan diameter (figure 3(c)) of Cu-CDs, which was mainly below 50 nm, correlated with size distribution on obtained Cu-CDs (figure 3(d)). This finding is supported by other reports that confirm that the particle size distribution of Cu-CDs and ordinary heteroatomic CDs was approximately 3-50 nm in diameter [38,41]. To strengthen the AFM data, morphology observation of the Cu-CDs is also supported by TEM images (Figure S1, supplementary material), which confirm the size diameter of CDs that are primarily below 50 nm.…”
Section: Resultssupporting
confidence: 87%
“…Next, morphology analysis of Cu-CDs shows the topographic images of Cu-CDs based on the AFM result, which demonstrated that the sperical topographic height (figures 3(a)-(b) dan diameter (figure 3(c)) of Cu-CDs, which was mainly below 50 nm, correlated with size distribution on obtained Cu-CDs (figure 3(d)). This finding is supported by other reports that confirm that the particle size distribution of Cu-CDs and ordinary heteroatomic CDs was approximately 3-50 nm in diameter [38,41]. To strengthen the AFM data, morphology observation of the Cu-CDs is also supported by TEM images (Figure S1, supplementary material), which confirm the size diameter of CDs that are primarily below 50 nm.…”
Section: Resultssupporting
confidence: 87%
“…The peaks at 1379 cm −1 and 1588 cm −1 , which refer to the D and G bands, respectively, reveal that GO was obtained from the synthesis process. 32–35 When compared with Raman spectra of bare cellulose, it could be understood that the obtained GO was utterly different from cellulose by the disappearance of the peaks at 1095 cm −1 and around 456 cm −1 , which are typical peaks for the C–O–C symmetric vibration and C–C–C ring deformation of cellulose, respectively. 36…”
Section: Resultsmentioning
confidence: 99%